THE EFFECT OF IMPLEMENTING A DEEP LEARNING APPROACH ON STUDENTS’ LEARNING OUTCOMES IN JUNIOR HIGH SCHOOL - Bambang Soepeno; Rully Putri Nirmala Puji; Jefri Rieski Triyanto; Dyah Ayu Puspitaningrum; Era Iswara Pangastuti (Adisam Publisher, 2026)
The purpose of implementing the deep learning approach is to create a learning process that is mindful, meaningful, and joyful. The objective of this study is to identify the effect of the deep learning approach on the learning outcomes of seventh-grade students. This study involved a total of 60 students divided into two classes. This study used a test as its research instrument. The results of the Independent T-test showed a significant difference between the scores of the experimental class (M = 26.86, SD = 3.58) and the control class (M = 19.46, SD = 4.02); t (7.51), p = 0.001. Thus, it can be concluded that the application of the deep learning approach has a significant effect on students’ learning outcomes. Based on the eta-squared results, deep learning also has a high-level effect on learning outcomes, with a value of 0.49. The implications of this study indicate that the implementation of deep learning contributes to the improvement of skills and creativity and makes learning more meaningful.